Tripartite Collaborative Institutions: Skema Konvergensi Institusi Untuk Mewujudkan Ketahanan Siber Indonesia - Fradhana Putra Disantara (Istinbath : Jurnal Hukum, 2021)
Cybercrime is a crime that is carried out systematically to damage or destroy computer networks, and will automatically have an impact on important data stored on the computer network. This article is written using a normative legal research method, with data sources in the form of primary legal materials and secondary legal materials, understood using a conceptual approach and a statute approach, then the data is analyzed qualitatively through deductive thinking. From the results of the research, it is known that the weakness of technical and non-technical infrastructure related to the network and information systems of a country is one of the reasons of cyber crime. So we need a defense concept that can overcome these weaknesses. The concept of cyber defense with tripartite collaborative institutions can be used as an option to strengthen cyber defense. With a system of cooperation between the Ministry of Defense, Kominfo, and BSSN. The Ministry of Defense focuses on cyber threats from abroad, the Ministry of Communication and Information focuses on cyber threats from within the country, while BSNN focuses on coordination, prevention, and handling of cyber crimes.